Smoky night - Bunting, Eve, 1928-2023.; Diaz, David (San Diego : Harcourt Brace, 1994)
When the Los Angeles riots break out in the streets of their neighborhood, a young boy and his mother learn the values of getting along with others no matter what their background or nationality.
Keywords: Riots -- California -- Los Angeles -- Juvenile fiction; Riots -- California -- Los Angeles -- Fiction; Interpersonal relations -- Fiction; Caldecott Medal; Neighborliness -- Fiction